CORRELATION COEFFICIENT AS A MATHEMATICAL SOLUTION OF ECONOMIC ISSUES - Madraximova Maxfuza Axmedovna; Turdaliyev Sodiqjon Muminjonovich; Abduraxmonov Dilmurod Akramaliyevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article provides information on determining the influence of factors of the production process in the economy through the correlation coefficients of mathematical statistics.